SHR2285, the first selectively oral FXIa inhibitor in China: Safety, tolerability, pharmacokinetics and pharmacodynamics combined with aspirin, clopidogrel or ticagrelor - Ma, Tingting; Dong, Yanli; Huang, Lei; Yang, Yuanxun; Geng, Yan; Fei, Fei; Xie, Pinhao; Zhao, Yu; Lin, Hui; Yang, Zeyu; Jin, Yun; Ju, Xitong; et al. (Frontiers in Pharmacology, 2022)
Purpose: To evaluate the safety, tolerability, pharmacokinetics and pharmacodynamics of SHR2285, the first oral coagulation factor XIa (FXIa) inhibitor developed in China in combination with aspirin, clopidogrel or ticagrelor in healthy subjects. Methods: This study was a single-center, randomized, double-blind, placebo-controlled (only SHR2285) design (NCT04945616). A total of 52 healthy subjects, 29 male and 23 female, were completed in this study. The subjects were divided into three groups: A, B and C, 16 subjects in group A (aspirin+clopidogrel+placebo or SHR2285 200 mg bid (1:3, 4 received placebo and 12 received SHR2285)), 16 subjects in group B (aspirin+clopidogrel+placebo or SHR2285 300 mg bid (1:3, 3 received placebo and 13 received SHR2285)) and 20 subjects in group C (aspirin+ticagrelor+placebo or SHR2285 300 mg bid (2:3, 8 received placebo and 12 received SHR2285)), respectively. All groups were administered orally for six consecutive days. Safety, tolerability, pharmacokinetics and pharmacodynamics parameters were assessed. Results: 1. SHR2285 was well tolerated, and all adverse events were mild. There was no evidence of an increased risk of bleeding. 2. After six days of twice-daily administration, SHR2285 could reach a steady state. The mean half-life of SHR2285 in group A, group B and group C was 13.9 h, 14.5 h and 13.8 h, respectively. 3. SHR2285 markedly inhibited FXI activity and prolonged activated partial thromboplastin time (APTT). In group A, group B and group C, the mean maximum inhibition rate of FXI activity was 84.8%, 89.3% and 92.2% and the mean maximum prolongation of APTT was 2.08-fold, 2.36-fold and 2.26-fold, respectively. Conclusion: These data suggest that SHR2285, a potential oral FXIa inhibitor, is expected to become a novel, safe and effective anticoagulant when combined with aspirin, clopidogrel or ticagrelor.